PENGARUH KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP KINERJA KEUANGAN DENGAN PENGUNGKAPAN LINGKUNGAN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar di BEI Tahun 2014-2018 - Saputra, Mas Findi Mulya (Pascasarjana Universitas Sultan Ageng Tirtayas, 2020)
This study aims to determine the effect of environmental performance and environmental costs on financial performance with environmental disclosure as an intervening variable. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. By using purposive sampling technique obtained 45 sample companies and analyzed using multiple linear regression. The results of this study indicate that (1) environmental performance has a positive effect on financial performance (2) environmental costs have no positive effect on financial performance (3) environmental disclosure has no positive effect on financial performance. (4) Environmental Performance has a positive effect on Environmental Disclosure. (5) Environmental Costs have no positive effect on Environmental Disclosure. (6) Environmental Performance against Financial Performance is mediated by Environmental Disclosures. (7) Environmental Costs to Financial Performance are not mediated by Environmental Disclosures.Keyword : Financial Performance, Environmental Performance, Environmental Costs, and Environmental Disclosures.